Socialization of students with mental retardation through rhymes and singing games - Ting, Hepzibeth T. (2005)
After systematic exposure to rhymes and singing games, the children with educable mental retardation were examined to determine socialization behavior changes. The children in the experimental group attained changes in all the ten components of socialization: accepting authority, coping with conflict, gaining attention, greeting others, helping others, making conversation, expressing oneself, responding to others, organized play, and playing informally. The results support the research trends that music therapy enhances the socialization behavior of special children. Teachers can use music to achieve non-musical goals
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Children with mental disabilities -- Education -- Philippines -- Manila; Special education -- Activity programs -- Philippines -- Manila; Singing games; Socialization